Peptic Ulcer and Gastric Cancer: Is It All in the Complex Host–Microbiome Interplay That Is Encoded in the Genomes of “Us” and “Them”? - Nath, Angitha N.; Retnakumar, R. J.; Francis, Ashik; Chhetri, Prakash; Thapa, Namrata; Chattopadhyay, Santanu (Frontiers in Microbiology, 2022)
It is increasingly being recognized that severe gastroduodenal diseases such as peptic ulcer and gastric cancer are not just the outcomes of Helicobacter pylori infection in the stomach. Rather, both diseases develop and progress due to the perfect storms created by a combination of multiple factors such as the expression of different H. pylori virulence proteins, consequent human immune responses, and dysbiosis in gastrointestinal microbiomes. In this mini review, we have discussed how the genomes of H. pylori and other gastrointestinal microbes as well as the genomes of different human populations encode complex and variable virulome–immunome interplay, which influences gastroduodenal health. The heterogeneities that are encrypted in the genomes of different human populations and in the genomes of their respective resident microbes partly explain the inconsistencies in clinical outcomes among the H. pylori-infected people.